Retrospective molecular integrated epidemiology of chagas disease in Colombia (2013)
American trypanosomiasis is a very complex zoonosis that is present throughout South America, Central America, and Mexico and continues to represent a serious threat to the health of countries in the region. The parasite infects 150 species from 24 families of domestic and wild mammals and shows remarkable genetic variability evinced in at least seven discrete typing units (DTU’s) named TcI–TcVI with the presence of a novel genotype associated with bats named TcBat. These DTUs show a wide range of geographical and host distributions. Our study aimed to establish the relationship between the genetic diversity of Trypanosoma cruzi and the diverse clinical manifestations of infected patients and unravel the molecular eco-epidemiology in the epizootic and enzootic scenarios in Colombia. We undertook intensive sampling in 17 departments of Colombia among 11 triatomine species, 9 mammalian reservoir species and humans and obtained 637 biological clones that were subsequently analyzed using nuclear and mitochondrial molecular markers. TcI was the most prevalent (80.7%) followed by TcII (7.2%), TcIII (3.9%), TcIV (5%), TcV (0.8%), TcVI (1.6%) and TcBat (0.8%). Within domestic foci, TcI (70%) was the most prevalent, followed by TcII (20%), TcIII (1.6%), TcIV (3.6%), TcV (2.2%) and TcVI (2,6%); within sylvatic foci, TcI (85%) was the most prevalent, followed by TcII (0.3%), TcIII (5.5%), TcIV (7%), TcVI (1.1%) and TcBat (1.1%). The results suggest the occurrence of the seven DTUs and strict associations of independent DTUs with the host and environment in Colombia. The implications are discussed herein.